2020
DOI: 10.14744/anatoljcardiol.2020.93213
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Serum Asymmetric Dimethylarginine Levels and Radial Artery Spasm

Abstract: Objective: The use of the radial approach in coronary angiography or percutaneous coronary intervention has increased owing to its advantages over the femoral approach such as rapid patient mobilization and improved patient comfort. However, radial artery spasm (RAS) that occurs during the procedure is a crucial factor in transradial approach failure and access site switch. Asymmetric dimethylarginine (ADMA) is a naturally occurring, modified amino acid that inhibits nitric oxide (NO) production. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“… 6 , 7 Moreover, a decrease in the NO levels, which is a vasoactive substance produced from the endothelium and plays an important role in vascular tonus, seems to be associated with RAS occurrence in patients undergoing TRA procedures. 13 Adropin increases the release of NO by increasing eNOS activity, causes vasodilation in the vessel wall with an indirect effect and has a potential endothelial protective role. Adropin plays a protective role against endothelial dysfunction by regulating eNOS expression through various growth factors and proteins.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 Moreover, a decrease in the NO levels, which is a vasoactive substance produced from the endothelium and plays an important role in vascular tonus, seems to be associated with RAS occurrence in patients undergoing TRA procedures. 13 Adropin increases the release of NO by increasing eNOS activity, causes vasodilation in the vessel wall with an indirect effect and has a potential endothelial protective role. Adropin plays a protective role against endothelial dysfunction by regulating eNOS expression through various growth factors and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in pheochromocytoma cells have suggested that ADMA can reduce the glutamate-induced cytotoxicity, apoptosis and Caspase-3 activation and reverse the down-regulation of glutamate-induced bcl-2 expression [ 16 ]. Also, it has been reported that ADMA levels may be increased in non-oncologic processes such as radial artery spasm, coronary artery disease and so on [ 17 , 18 ]. Although, ADMA plays a significant role in promoting tumor progression in colon cancer and esophageal cancer, the role of ADMA in gastric cancer has not been well investigated.…”
Section: Introductionmentioning
confidence: 99%